Preoperative anxiety and satisfaction with information provided by nursing staff and anesthesiologists in oncological patients - Intas, George; Tsolakoglou, Ioannis; Papadaki, Chrysi; Stergiannis, Pantelis (Health & Research Journal, 2025)
Background: A surgical procedure is accompanied by some degree of perioperative risk, which creates a state of anxiety. The aim of this study was to investigate the correlation between preoperative anxiety and satisfaction with the provided information by nursing staff and anesthesiologists in oncological patients. Method and Material: This cross-sectional study was conducted among adult oncology patients scheduled for surgery at a large university hospital in the Peloponnese. Participants were randomly selected to form the study population. The time of study was between November 2023 and February 2024. Data collection was done with the State Anxiety Inventory (STAI) and the Information Satisfaction Questionnaire (ISQ). The statistical analysis of the data was done with the statistical program SPSS v. 25.0. Results: The study sample consisted of 100 patients with a mean age of 50.3 ± 16 years. The majority of participants expressed a preference for receiving comprehensive information and for being actively involved in decisions regarding their care. They also reported that they had been provided with the best possible information. In terms of anxiety, Most participants (over half) were found to have moderate levels of anxiety, while approximately two in ten exhibited elevated anxiety. Older age (p = 0.003) and lower stress levels (p = 0.033) were significantly associated with higher satisfaction regarding the information provided. Conclusions: Patient satisfaction with the provided information by the nursing staff and the anesthesiologists reduces pre-surgical anxiety.